A World Grown Strange: A Summons to Teachers of Literature - Wood, Ralph C. (Christianity & literature, 2021)
The calamities of our dystopian time tempt teachers of literature either to a stiff defense of traditional Western civilization or else to a flaccid acceptance of post-modernist relativism. This essay argues that both strategies are mistaken. Since for post-modernists no tradition can be definitive, they are obliged to welcome Christians to voice our own history-laden tradition in a tournament of narratives. I buttress this claim by reference to the lessons that Flannery O’Connor learned, albeit imperfectly, about the intrinsic claims of art that must not be suborned to anything extrinsic, not even to unprecedented evils.